Perceptions of Inclusion in Australian Schools - Sean Kearney (Iranian Journal of Educational Research)
Objective: This study explores educational professionals’ perceptions of inclusive practices in New South Wales (NSW), Australia, with a focus on specialized roles such as learning support coordinators, teachers, and school learning support officers. Methods: Using surveys and interviews, the research investigates how inclusion is conceptualized, implemented, and its perceived impact on students. Results: Findings highlight significant inconsistencies in understanding inclusion, with some participants associating it exclusively with students with additional needs, while others embrace a broader philosophy. Despite general support for inclusive practices, challenges persist, including limited resources, insufficient professional development, and variability in leadership support. Comparisons with international research underscore shared challenges in operationalizing inclusive education globally. Conclusions: This paper proposes a framework for reconceptualizing inclusion as a universal pedagogical philosophy and offers actionable recommendations for bridging the gap between policy and practice. Implications for teacher training and professional development are also discussed.